Understanding physics (John Wiley & Sons, 2002)
Using an interactive learning strategy, this text provides a hands on introduction to the fundamentals of Physics. Built on the foundations of Halliday, Resnick, and Walker’s FUNDAMENTALS OF PHYSICS 6e, this text represents the latest methods in physics instruction. Incorporating new approaches based upon Physics Education Research (PER), this book is designed for courses that use computer-based laboratory tools, and promote Activity Based Physics in lectures, labs, and recitations.